2002
DOI: 10.1034/j.1399-6576.2002.460502.x
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular changes during anesthesia: sevoflurane compared with propofol

Abstract: The decreased CFC in response to sevoflurane may result in less extravasation of fluids into the interstitial space, thereby reducing intraoperative fluid requirements. These data suggest that sevoflurane may be the preferred anesthetic agent in subjects susceptible to large intraoperative fluid shifts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 20 publications
2
34
0
2
Order By: Relevance
“…A protocol was subsequently established in which it was recommended that surgery be performed by two anesthetists using balanced general anesthesia because of the benefits of sevofluorane on microcirculation and the protective factor in injury due to ischemiareperfusion. Analgesia was performed with remifentanyl because its pharmacokinetic and pharmacodynamic characteristics allow for greater hemodynamic stability and a short half-life allows us to adapt rapidly to significant hemodynamic changes [1,14,17,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A protocol was subsequently established in which it was recommended that surgery be performed by two anesthetists using balanced general anesthesia because of the benefits of sevofluorane on microcirculation and the protective factor in injury due to ischemiareperfusion. Analgesia was performed with remifentanyl because its pharmacokinetic and pharmacodynamic characteristics allow for greater hemodynamic stability and a short half-life allows us to adapt rapidly to significant hemodynamic changes [1,14,17,21].…”
Section: Discussionmentioning
confidence: 99%
“…Tissues to be transplanted undergo primary ischemia, whose severity and seriousness is proportional to time, which is tolerated differently by different tissues and which we cannot influence [16,17]. We will use as a basis the anesthetic management of reconstructive microsurgery that is most similar combining it with the anesthetic techniques of other solid organ transplants [16,18,19].…”
Section: Anesthetic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bruegger i wsp. [19], używając pomiarów pletyzmograficznych, badali oddziaływanie sewofluranu i propofolu na parametry mikrokrążenia w kończynach dolnych, stwierdzając brak wpływu tych środków na przepływ i odkrywając jedynie zmniejszenie współczynnika filtracji we włośnicz-kach przez sewofluran, co powoduje mniejszą utratę płynów do przestrzeni śródmiąższowej. W obu grupach stwierdzili również obniżone ciśnienie żylne podczas podtrzymania znieczulenia, co nie wydaje się zaskakujące.…”
Section: Dyskusjaunclassified
“…Furthermore, little is known about how anesthetics affect microvascular parameters related to fluid distribution 23 . It has been shown that sevoflurane, compared with intravenous anesthetics such as propofol, may have beneficial effects on microcirculation, reducing plasma leakage into interstitial space and, therefore, decreasing the edema 24 . Some authors also report that it may have a protective effect on endothelial cells against ischemia-reperfusion 25 .…”
Section: The Techniquementioning
confidence: 99%